PUBLIC SERVICE MOTIVATION AS AN INTERVENTION VARIABLE OF SELF-EFFICACY, COMPETENCE, AND ORGANISATIONAL COMMITMENT ON STATE APPARATUS PERFORMANCE - Suma, Dewi; Siregar, Budi Alamsyah (Strategic Management Business Journal, 2023)
This study examines the impact of service motivation as a mediating variable for self-efficacy, competence and organizational commitment on the performance of the State Civil Apparatus. A random sampling approach was used to randomly select 209 respondents. Questionnaires were used to collect data. SEM-PLS with structural equation modelling (SEM) was used for data analysis. Service motivation is the most dominant variable in influencing performance. It is recommended for policy makers to motivate the State Civil Service Apparatus in terms of carrying out their work, having good health in carrying out their duties, having more confidence, having high integrity, being skilled in carrying out tasks, being able to adapt to colleagues well. Furthermore, it is also necessary to increase the role of self-efficacy, competence, training, and commitment from the organization, so that all supporting components to improve performance can go hand in hand for the progress of the organization. JEL CLASSIFICATION: M50, O15